Beyond Discourse: Notes on Spatial Agency - Tatjana Schneider; Jeremy Till (Footprint)
This article investigates the word ‘agency’ in relation to the role, responsibility and power of the architect. Using Anthony Giddens’s formulation of agency, we discuss the transformative potential of architecture where the lack of a predetermined future is seen as an opportunity and not a threat. Four episodes describe related instances of architectural practice as spatial agency: muf, OSA, Santiago Cirugeda and The New Architecture Movement. The paper concludes with an urgent call for architects to face up to their political and environmental responsibilities.